The Longissimus Capitis Insertion as a Superficial Landmark for the Sigmoid Sinus: An Anatomical Study - Iwanaga, Joe; Watanabe, Koichi; Khan, Pervez A.; Nerva, John D.; Amenta, Peter S.; Dumont, Aaron S.; Tubbs, R. Shane (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Many external anatomical landmarks have been used for approximating deeper, intracranial structures. Herein, we evaluate the attachment of the longissimus capitis (LC) on the mastoid process as a landmark for the underlying sigmoid sinus.Methods Adult cadavers underwent dissection of the posterior occiput with special attention to the attachment of the LC muscle. Once the periphery of the muscle's tendon of attachment was determined, a burr hole was made in this area and evaluated internally for its relationship to the sigmoid sinus.Results From an intracranial view, burr holes on all sides were over the sigmoid sinus and just slightly lateral to the center of the sinus. The distance from the midline to the medial border of the insertion of the LC had a mean of 63.0 ± 7.2 mm. The width of the tendon of insertion of the LC on the mastoid process had a mean of 17.6 ± 5.7 mm. The length of the tendon insertion of the LC had a mean of 14.7 ± 4.7 mm. The distance from the inferior border of the insertion of the LC to the tip of the mastoid process had a mean of 6.2 ± 4.5 mm.Conclusion To our knowledge, use of the attachment site of the LC on the mastoid process as an external landmark for the underlying sigmoid sinus has not previously been reported. Based on our cadaveric findings, the sigmoid sinus is centered under the attachment of the LC regardless of the width of its tendon.
Keywords: posterior cranial fossa; anatomy; longissimus capitis; craniotomy; transmastoid; neurosurgery